Characterization of the complete mitochondrial genome of Notonecta amplifica Kiritshenko, 1930 (Hemiptera: Notonectidae) and its phylogenetic implications. Issue 1 (2nd January 2022) - Li, Min; Lei, Ting; Wang, Guobin; Wang, Luming
Abstract: The complete mitochondrial genome of Notonecta amplifica Kiritshenko, 1930 (Hemiptera: Notonectidae) was sequenced by high-throughput sequencing (HTS). The whole length is 15, 150 bp, including 13 protein-coding genes (PCGs), 22 transfer RNA (tRNAs), two ribosomal RNA (rRNAs) and a 528 bp control region (D-loop). The nucleotide is with a base composition of A (43.01%), G (10.32%), C (13.87%) and T (32.80%). The total length of the coding sequences encoding 3, 694 amino acids is 11, 113 bp, accounting for 73.35%. The lengths of 12S rRNA and 16S rRNA are 800 and 1, 251 bp, respectively. The Bayesian phylogenetic analysis of 20 taxa indicate that N. amplifica is closely related to Notonecta montandoni, with posterior probability value of 1.00. The complete mitochondrial genome sequence would provide useful genetic information for future taxonomic and phylogenetic classification of N. amplifica .